Creating a Hoosier Self-Portrait : The Federal Writers' Project in Indiana, 1935-1942 - Blakey, George T. (Book collections on Project MUSE., 2005)
"From 1935 to 1942, the Indiana office of the Federal Writers' Program hired unemployed writers as "field workers" to create a portrait in words of the land, the people, and the culture of the Hoosier state. This book tells the story of the project and its valuable legacy."--Jacket